The Economic Effects of COVID-19 and Credit Constraints: Evidence from Italian Firms' Expectations and Plans - Pierluigi Balduzzi; Emanuele Brancati; Marco Brianti; Fabio Schiantarelli (Institute of Labor Economics (IZA), 2020)
We investigate the economic effects of the COVID-19 pandemic and the role played by credit constraints in the transmission mechanism, using a novel survey of expectations and plans of Italian firms, taken just before and after the outbreak. Most firms revise downward their expectations for sales, orders, employment, and investment, while prices are expected to increase at a faster rate, with geographical and sectoral heterogeneity in the size of the effects. Credit constraints amplify the effects on factor demand and sales of the COVID-19 generated shocks. Credit-constrained firms also expect to charge higher prices, relative to unconstrained firms. The search for and availability of liquidity is a key determinant of firms' plans. Finally, both supply and demand shocks play a role in shaping firms' expectations and plans, with supply shocks being slightly more important in the aggregate.
Keywords: E2; E3; G30; I10; 330; COVID-19; pandemic; firms' expectations; firms' plans; credit constraints; prices; employment; investment; sales; orders